2015
DOI: 10.24102/ijafr.v3i4.381
|View full text |Cite
|
Sign up to set email alerts
|

Actual and Potential Applications of Moringa stenopetala, Underutilized Indigenous Vegetable of Southern Ethiopia: A Review

Abstract: Moringa stenopetala, locally called Haleko, is an indigenous vegetable tree native to southern Ethiopia and grown mainly for its food value. It is a drought tolerant and fast growing tree that has high nutritional value and the potential to alleviate malnutrition in the tropics. Millions of people in southern Ethiopia consume its leaves as a staple vegetable. It also has potential medicinal and industrial applications and significant economic contributions. Despite its actual and potential roles, M. stenopetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 30 publications
1
34
0
3
Order By: Relevance
“…In addition, because the species are resistant to drought, Moringa species become valuable during the dry season when other vegetables are not available. In fact, M. stenopetala can be found in all households in the Gamo Gofa zone (Seifu, 2014 ). Mathur ( 2005 ) stated in his book that Moringa leaves are highly nutritious, with two times more protein than yogurt, four times more vitamin A than carrots, three times more potassium than bananas, seven times more vitamin C than oranges, and four times more calcium than milk.…”
Section: Traditional Usesmentioning
confidence: 99%
“…In addition, because the species are resistant to drought, Moringa species become valuable during the dry season when other vegetables are not available. In fact, M. stenopetala can be found in all households in the Gamo Gofa zone (Seifu, 2014 ). Mathur ( 2005 ) stated in his book that Moringa leaves are highly nutritious, with two times more protein than yogurt, four times more vitamin A than carrots, three times more potassium than bananas, seven times more vitamin C than oranges, and four times more calcium than milk.…”
Section: Traditional Usesmentioning
confidence: 99%
“…Many different ecotypes and varieties of M. stenopetala are found in Ethiopia. M. stenopetala is an important indigenous vegetable in southwestern Ethiopia where it is cultivated as a food crop 1. The fresh leaves are cooked and consumed by the local communities.…”
Section: Introductionmentioning
confidence: 99%
“…In southern Ethiopia, the leaf of the plant is used as a substitute for cabbage in the local diet and as animal feed. It has been demonstrated that it is rich in carbohydrates, proteins, fats, minerals and fiber (35). Studies have also shown that the plant is a reasonably good natural purifier of muddy and contaminated water.…”
Section: Moringa Sppmentioning
confidence: 96%